The newspaper heading and proper name are parts of medial space - Baturina, Lyudmila Aleksandrovna; Lepikhov, Nikolay Vladimirovich; Panova, Elena Pavlovna; Popova, Anastasiia Valerjevna; Karpova, Galina Gelevna; Gumerova, Liliya Zufarovna (Linguistics and Culture Review, 2021)
In article the basic components of modern medial space are examined: heading and proper name. Authors emphasize that the heading in the modern Internet - newspaper text influences the reader and forces to pass under the reference to the publication which is interested by him. Besides it, the basic functions of heading and proper name as parts of the journalese text are analyzed. All theoretical moments of functioning onims in newspaper headings, authors of the article illustrate concrete examples. Researchers judge that proper name had in newspaper headings are used with a support on (background knowledge) reader that allows to draw quickly his attention to the publication.